Evaluasi Gameplay SimCity Mobile Game Menggunakan Mechanic Dynamic Aesthetic Framework - Fajrian Muchtar; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
SimCity Mobile is a game that was developed by the mobile version after the game of the same name was previously released on the PC platform. This game is one of the games that has a large number of players, so far it has been investigated and touched 50 million downloaders. With this increasingly massive growth, it is found that game developers make games with the same genre and have different gameplay from one another. To maintain the popularity that SimCity has, an evaluation is needed to assess the extent to which the developers of the SimCity Mobile game present gameplay that is enjoyed by players. The results of the evaluation can also be used as a reference in developing the game going forward. One of the evaluation methods that can be used is to use Mechanic, Dynamic, Aesthetic Framework. In the mechanical aspect one of them is the use of microtransaction which can change the gameplay process of the player, where players who buy virtual money are more facilitated in the mission or task done. Then in the dynamic side, where players can process the sale of items but cannot negotiate. The last is the aesthetic aspect, where players feel the gameplay is repetitive